Impact of upstream variability on the Loop Current dynamics in numerical simulations of the Gulf of Mexico - Laxenaire, Rémi; Chassignet, Eric P.; Dukhovskoy, Dmitry S.; Morey, Steven L. (Frontiers in Marine Science, 2023)
The Loop Current (LC), which is the main mesoscale dynamic feature of the Gulf of Mexico (GoM), has a major impact on the circulation and its variability in the interior Gulf. The LC is a highly variable and dynamic feature. It changes shape from a short jet connecting the two openings of the GoM in an almost straight line ("retracted phase") to a long loop invading most of the eastern part of the GoM ("extended phase"). When it is in the extended phase, it can shed large anticyclonic eddies, called Loop Current Eddies, which then migrate to the western GoM. In this study, the processes controlling the LC dynamics are investigated using two multi-decadal simulations of the Gulf of Mexico HYbrid Coordinate Ocean Model differing in their open boundary conditions (BCs) and altimetry-derived gridded fields. The LC in the simulation with BCs derived from monthly climatology state variables frequently remains in its retracted phase significantly longer than observed. In contrast, the duration of the retracted phase is notably shorter in the simulation in which the BCs have realistic daily variability. By examining the flow properties through the Yucatan Channel from which the LC originates, we find that increased intensity of this current and a westward shift of the mean core is associated with the LC transitions from the retracted to the extended phase. This transition is accompanied by an increase of both cyclonicity of the flow in the west and anticyclonicity in the east of the core of this jet. Moreover, the number of anticyclonic eddies entering in the GoM through the Yucatan Channel is significantly higher when the LC extends in the GoM. Consequently, this study demonstrates the importance of realistic flow variability at the lateral boundaries for accurate simulation of the LC system in a model, and reveals characteristics of the upstream flow associated with different LC behavior that can potentially aid in forecasting the LC system.